Prevalence of Acute Kidney Injury in Patients with Sepsis in Isfahan, Iran - Mehdi Kazemi (Urology Research Center, 2021)
Introduction: Acute kidney injury (AKI) is one of the most prevalent and extreme physio-pathological disorders in hospitalized patients, 20-40% of whom are hospitalized in the intensive Care Unit (ICU). Sepsis is the most commonplace reason for AKI in intensive care patients, accounting for 50% of ICU cases Methods: This was a descriptive cross-sectional study conducted at Isfahan University of Medical Sciences from 22 October 2016 to 22 October 2017. Two hundred and thirty-two selected patients at Al-Zahra Hospital in Esfahan were enrolled in the study. Patients were followed for 10 days to determine the short-term mortality rate. Data were analyzed using t-test and Chi-squared test using SPSS software (ver. 16). Results: In this study, 232 patients with sepsis were evaluated. Their mean age (± standard deviation) was 69.9 (18.4) years. The mean age of patients with acute kidney Injury (72.7 years) was significantly higher than the mean age of non-patients (non-AkI) (66.6 years) (p-value= 0.012). However, the significant difference was not between the age groups, but the p-value was near the significant border. The mortality rate of patients (53.6%) was significantly higher than the non-patients (non-AKI) (29.6%) (p-value<0.0001). Conclusions: This study showed that the prevalence of AKI was 57.3%, which was similar to the prevalence rate in other countries. A relationship was also demonstrated between AKI and mortality rate and showed that AKI increases the mortality rate.